SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN OBJEK WISATA MENGGUNAKAN METODE AHP BERBASIS JAVA Study Kasus: Dinas Kebudayaan, Pariwisata, Pemuda & Olahraga Kabupaten Aceh Tengah - Richasanty Septima S (STEKOM PRESS, 2020)
Department of Culture , Tourism , Youth and Sports Central Aceh district especially in tourism is in charge of managing and developing infrastructure for tourism, the selection of a tourist attraction right capable of giving the best decision with the information on the sights with AHP ( Analytical Hierarchy Prsocess ) that match the criteria , Election Decision Support System using AHP Attractions Java based , Using Netbeans and MySQL as data storage .